Biochemical Resistance Mechanism of Several Genotype of Soybean to Rust Diseases - Moh Setyo Purwoko; Endang Budi Trisusilowati; Amarullah . (UNEJ e-Proceeding, 2014)
The research to identify of the content of Fenol and Flavonoid compounds which set as phytoalexin of several soybean genotype from rust diseases. Four genotypes of soybean which were examined at Unej-1, Unej-2 (moderate resistance), Burangrang (tolerance) and Lokon (susceptible). Based on rating code of IWGSR Unej-1, Unej-2 and Burangrang were proved moderate resistance and Lokon which was considered susceptible reality showed moderate susceptible. At Unej-1, Unej 2 and Burangrang which moderate resistance showed an increase of amount of Fenol and Flavonoid compounds greather than Lokon which was moderate susceptible Keywords: Biochemical Resistance, Soybean and Rust diseases